Opportunities to Enhance Linkage to Hepatitis C Care Among Hospitalized People With Recent Drug Dependence in New South Wales, Australia: A Population-based Linkage Study. (9th June 2021) - Valerio, Heather; Alavi, Maryam; Law, Matthew; McManus, Hamish; Tillakeratne, Shane; Bajis, Sahar; Martinello, Marianne; Matthews, Gail V; Amin, Janaki; Janjua, Naveed Z; Krajden, Mel; George, Jacob; et al.
Abstract: Background: People who inject drugs are at greater risk of hepatitis C virus (HCV) infection and hospitalization, yet admissions are not utilized for HCV treatment initiation. We aimed to assess the extent to which people with HCV notification, including those with evidence of recent drug dependence, are hospitalized while eligible for direct-acting antiviral (DAA) therapy, and treatment uptake according to hospitalization in the DAA era. Methods: We conducted a longitudinal, population-based cohort study of people living with HCV in the DAA era (March 2016–December 2018) through analysis of linked databases in New South Wales, Australia. Kaplan-Meier estimates were used to report HCV treatment uptake by frequency, length, and cause-specific hospitalization. Results: Among 57 467 people, 14 938 (26%) had evidence of recent drug dependence, 50% (n = 7506) of whom were hospitalized while DAA eligible. Incidence of selected cause-specific hospitalization was highest for mental health-related (15.84 per 100 person-years [PY]), drug-related (15.20 per 100 PY), and injection-related infectious disease (9.15 per 100 PY) hospitalizations, and lowest for alcohol use disorder (4.58 per 100 PY) and liver-related (3.13 per 100 PY). In total, 65% (n = 4898) of those who were hospitalized had been admitted ≥2 times, and 46% (n = 3437) were hospitalized ≥7 days. By the end of 2018, DAA therapy was lowest for those hospitalized ≥2 times, for ≥7 days, and those whose first admission was for injection-related infectious disease, mental health disorders, and drug-related complications. Conclusions: Among people who have evidence of recent drug dependence, frequent hospitalization—particularly mental health, drug, and alcohol admissions—presents an opportunity for engagement in HCV care. Abstract : We aimed to assess the extent to which people with hepatitis C virus (HCV) notification, including those with evidence of recent drug dependence, are hospitalized while eligible for direct-acting antiviral (DAA) therapy, and treatment uptake according to hospitalization in the DAA era.